Sustainable tourism development prac-tices of mice venue providers in east coast region, peninsula Malaysia / Maisarah Abd Hamid... [et al.] - Abd Hamid, Maisarah; Ismail, Noralisa; Mohd Fuza, Zatul Iffah; Ahmad, Khairun Najiah; Awang, Khairil Wahidin (2013)
The main purpose of this study is to review the sustainable tourism development practices of MICE (Meeting, Incentive, Convention and Exhibition) at hotel venues in East Coast Region, Peninsula Malay-sia. Responding to the importance of sustainable tourism practices, Malaysia has started to apply such practices in all tourism products, which include the hotel facilities. Malaysia offers a range of MICE venues that are either purposely built or integrated with hotel facili-ties. As one of the fastest emerging MICE tourism destination in the region, the sustainable tourism development practices by MICE venue providers is almost a must. The implementation of sustainable practices will bring benefits to the industry. However, it requires participation from all stakeholders in revising specific guidelines or following already accepted best practices to ensure the viability of the sustainable tourism concept. Most of the MICE venues in the East Coast Region, Peninsula Malaysia have the potential to apply sustainable tourism development practices in their day to day opera-tion. The result of this study will be used to propose guidelines for sustainable tourism development practices in MICE tourism.